Spectrophotometric Determinations of Sulfacetamide Following Simple Diazotization and Coupling with Chromotropic Acid - Darweesh, Samar A.; Al-Haidari, Ibdul Mohsin A.; Mohammed, Alaa K.; Dikran, Sarmad B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A simple, sensitive, accurate and economic spectrophotometric method has been developed for the determination of sulfacetamide (SFA) in pure form, synthetic sample and urine. The method is based on diazotization of primary amine group of sulfacetamide with sodium nitrite and hydrochloric acid followed by coupling with chromotropic acid in alkaline medium to obtain a stable orange colored chromogen which exhibit a maximum absorption (λmax) at 511.5 nm. Different variables affecting the completion of reaction have been carefully optimized following the classical univariate sequence and modified simplex method (MSM). Under optimized conditions, Beer’s law obeyed in the concentration range of (0.5- 20.0 µg.ml-1) with molar absorptivity of 3.2186*104 L.mol-1.cm-1. The limit of detection was 0.054 µg.mL-1 and Sandell’s sensitivity value 7.8989 µg.cm-2. The proposed method was successfully applied to the determination of (SFA) in synthetic sample and urine.